Improved production of recombinant β-mannanase (TaMan5) in Pichia pastoris and its synergistic degradation of lignocellulosic biomass - Zheng, Fengzhen; Basit, Abdul; Zhang, Zhiyue; Zhuang, Huan; Chen, Jun; Zhang, Jianfen (Frontiers in Bioengineering and Biotechnology, 2023)
Mannan, a highly abundant and cost-effective natural resource, holds great potential for the generation of high-value compounds such as bioactive polysaccharides and biofuels. In this study, we successfully enhanced the expression of constructed GH5 β-mannanase (TaMan5) from Trichoderma asperellum ND-1 by employing propeptide in Pichia pastoris. By replacing the α-factor with propeptide (MGNRALNSMKFFKSQALALLAATSAVA), TaMan5 activity was significantly increased from 67.5 to 91.7 U/mL. It retained higher activity in the presence of 20% ethanol and 15% NaCl. When incubated with a high concentration of mannotriose or mannotetraose, the transglycosylation action of TaMan5 can be detected, yielding the corresponding production of mannotetraose or mannooligosaccharides. Moreover, the unique mechanism whereby TaMan5 catalyzes the degradation of mannan into mannobiose involves the transglycosylation of mannose to mannotriose or mannotetraose as a substrate to produce a mannotetraose or mannopentose intermediate, respectively. Additionally, the production of soluble sugars from lignocellulose is a crucial step in bioethanol development, and it is noteworthy that TaMan5 could synergistically yield fermentable sugars from corn stover and bagasse. These findings offered valuable insights and strategies for enhancing β-mannanase expression and efficient conversion of lignocellulosic biomass, providing cost-effective and sustainable approaches for high-value biomolecule and biofuel production.